Physico-chemical quality of fish products marketed in Colombia - Carrera, Silvia; Gutiérrez, Nelson; Girón, Joel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The nutritional characteristics of fish products have positioned them as one of the fastest growing food categories worldwide. Additionally, for developing innovative foods, it is crucial to understand the physico-chemical properties of commercial products and to be familiar with the food industry regulations that determine the criteria and specifications for new developments. For this purpose, frequency questionnaires were applied to fish products marketed in the retail sector. Additionally, processed products were selected for analytical determinations of moisture, NaCl content, and water activity. The results showed that 80% of the products are marketed in large supermarkets with 20% in local markets. It was also observed that 79% of the products are of national origin. The highest salt contents on a dry basis ( 48%) were determined on smoked salmon and salted-smoked herring samples, while tilapia patties showed the lowest NaCl values on a dry basis 6%. Within the Colombian market, products with a high degree of processing are imported and they contain higher salt contents. The national product offers low processing levels, being mainly frozen fillets. This opens the possibility for the development of innovative products using local raw materials.